Thrombospondin and VEGF-R: Is There a Correlation in Inflammatory Bowel Disease?. (18th July 2013) - Wejman, Jaroslaw; Pyzlak, Michal; Szukiewicz, Dariusz; Jarosz, Dorota; Tarnowski, Wieslaw; Szewczyk, Grzegorz
Abstract : Up to date several authors discussed interactions between cells forming inflammatory infiltrates in the course of inflammatory bowel disease (IBD), mainly dealing with endoscopic biopsy specimens. These usually contain only mucosa. We have evaluated full bowel wall sections, which seems to be especially important in patients with Crohn's disease (CD). The purpose of our study was to evaluate the relationship between vascular density and expression of thrombospondin-1 (TSP-1) and vascular endothelial growth factor receptor 1 (VEGFR-1) in full-thickness tissue fragments of intestinal wall taken from patients after colectomy, comparing those with IBD to non-IBD control group. Histological sections were immunostained with antibodies against CD-31, TSP-1, and VEGFR-1 and analyzed by pathologists with the use of computer-assisted morphometrics. Our research showed significantly higher vascular density and vascular area percentage in all layers of bowel wall in patients with CD when compared to control. We have also demonstrated differences in vascular density distribution between ulcerative colitis (CU) and CD and between CU and control. However we have not found statistically significant correlation between those findings and VEGFR-1 or TSP-1 expression. Our results might suggest existence of different, TSP-1 independent pathways of antiangiogenesis in IBD.